What works in residential care: making it work - Lesley Archer (Scottish Journal of Residential Child Care)
What works in residential care is complex. The quality of practice does not just depend on how care workers operate with, and on behalf of, the young people they look after. Quality of care depends also on how residential care and its staff are regarded and worked with by the parent organisation and the networks that surround each young person and each residential establishment. In order to understand what works and how to make it work, residential workers, field social workers and managers have to work together with young people, their families, and members of other networks such as schools and health services.